1994
DOI: 10.1111/jon199442104
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Positron Emission Tomographic Evaluations of Brain Metabolism in Acute Herpes Encephalitis

Abstract: This first known positron emission tomography report on metabolic changes in acute herpes simplex virus (HSV-1) encephalitis demonstrates focal hypermetabolism in areas of cerebral cortex adjacent to actively inflamed hippocampus acutely infected with HSV-1. When neuropsychiatric symptoms recurred in a previously healthy 61-year-old patient 1 month after recovering from acute HSV-1 encephalitis, repeat positron emission tomography with fluorodeoxyglucose was helpful in ruling out recurrent active infection by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 5 publications
1
12
0
2
Order By: Relevance
“…FDG hypermetabolism converting to hypometabolism on a followup examination has already been described, but in a case of herpetic encephalitis [9]. Anyway, this possibility has been excluded in our patient by HSV serology, and a possible epileptic activity was excluded as well.…”
Section: Discussionmentioning
confidence: 77%
“…FDG hypermetabolism converting to hypometabolism on a followup examination has already been described, but in a case of herpetic encephalitis [9]. Anyway, this possibility has been excluded in our patient by HSV serology, and a possible epileptic activity was excluded as well.…”
Section: Discussionmentioning
confidence: 77%
“…Suspicion of the disease may emerge in patients with rapidly progressive dementia and multifocal signs. It is of utmost importance to obtain a diagnosis as early as possible since some types of rapidly progressive dementia may be associated with treatable diseases (autoimmune, paraneoplastic or viral encephalitis) [1,2,3,4]. The diagnosis of definite CJD is at present only possible through neuropathological examination of brain tissue according to international (WHO and EU) consensus.…”
Section: Introductionmentioning
confidence: 99%
“…The mean CBF counts significantly decreased. Previous SPECT and PET studies in cases of herpes and influenza encephalitis showed similar findings; that is, a decrease of CBF or cerebral glucose metabolism following disappearance of clinical symptoms and CSF findings of inflammation 17–20 17–20 …”
Section: Discussionmentioning
confidence: 60%
“…Previous SPECT and PET studies in cases of herpes and influenza encephalitis showed similar findings; that is, a decrease of CBF or cerebral glucose metabolism following disappearance of clinical symptoms and CSF findings of inflammation. [17][18][19][20] These reports speculated that functional neuroimaging techniques could detect the inflammation-related hyperactivity of the brain. [17][18][19][20] These findings suggest that in cases of general paresis, the decrease of quantitative CBF counts following the penicillin treatment reflects the disappearance of encephalitis caused by the infection with Treponema pallidum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation